Autotrophic in vitro culture method, inoculated with native arbuscular mycorrhizae, for the adaptation of trap plants of the Asteraceae family - Naranjo-Moran, Jaime (2025)
The implementation of autotrophic in vitro culture systems is revealed as a crucial strategy for the multiplication of native arbuscular mycorrhizal fungi, as it plays a fundamental role in restoring the sustainability of agricultural systems that have suffered degradation. The objective of the research was to establish an autotrophic in vitro culture method using two trap plants of native arbuscular mycorrhizal fungi under laboratory conditions. Inoculum native to Bidens pilosa and Tagetes patula were collected, spores were disinfected and cultured in vitro using a modified Murashige and Skoog medium. The results showed mycorrhization percentages greater than 50% in the trap plants and a significant reduction in microbial contamination with the use of antibiotics. The autotrophic in vitro culture system was feasible with Tagetes patula and Bidens pilosa, proving to be a promising strategy to produce mycorrhizal inoculum under laboratory conditions. In conclusion, spore disinfection and selection of suitable trap plants guarantee the success of in vitro culture inoculated with native arbuscular mycorrhizal fungi.